(untitled) (Orfeu, 2019)
This paper focuses on the analysis of the Brazilian song called Modinha as musical historical research to improve an understanding of Brazilian contemporary society, with the bibliography of Mário de Andrade. It is also aimed to draw a parallel between this music of Imperial Brazil and Brazilian popular music of the twentieth century and the present day, looking for examples of composers and performers who have maintained the tradition of Modinha, and songs with similar social collective functions as the samba-song of the 1930s. In this way, the results were achieved through analyzes poems and lyrics of Modinhas, relating them to their historical contextualization, enabling a survey of the social groups that produced them and the continuity of the tradition in posterity. The analysis of Mário de Andrade´s “Viola quebrada” made possible to contextualize the research on Ethnomusicological survey, regarding Brazil as a country that was appropriated by the Portuguese without being considered with its particular features, and how this metaphor is employed poetically.